CALCAREOUS PLANKTON BIO-EVENTS IN THE MIOCENECASE PELACANI SECTION (SOUTH-EASTERN SICILY, ITALY) - DI STEFANO, ENRICO; BONOMO, SERGIO; CARUSO, ANTONIO; DINARES-TURELL, JAUME; MARIA FORESI, LUCA; SALVATORINI, GIANFRANCO; SPROVIERI, RODOLFO (Milano University Press, 2002)
The upper Serravallian-Lower Tortonian Case Pelacani section in Sicily is represented by the epipelagic sediments of the Tellaro Formation. Along the section, which was sampled in four easily correlatable segments, a more or less continuous sequence of lithologic couplets, with whitish marls and blackish levels in the lower part and whitish marls and whitish more indurated levels in the upper part are present. The distribution of the most common taxa of planktonic foraminifera and calcareous nannofossils was quantitatively estimated in 316 samples, collected every 20 cm along the section which is 66.35 m thick. This allowed to identify eleven planktonic foraminifera (but only the eight marker events were quantitatively estimated) and five calcareous nannofossil bio-events. Their astrochronology is reported by correlation with the cyclostratigraphic results obtained for this section in a different paper. The ages are well comparable with the ages published for the same events in other Mediterranean sections. Paleomagnetic analysis along 30 meters in the central part of the section gave puzzling results and therefore no reliable magnetostratigraphy could be obtained. The Case Pelacani section, straddling the stratigraphic interval between slightly below the first occurrence and slightly above the first regular occurrence of Neogloboquadrina acostaensis , is a good candidate for the definition of the GSSP (Global Stratigraphic Section and Point) of the Tortonian. Independently from the selected section, we suggest to define the Serravallian/Tortonian boundary in a level coincident or near the last occurrence of Paragloborotalia siakensis, as already proposed, or coincident with or near the last common occurrence of Globigerinoides subquadratus. This latter level virtually coincides with the first common occurrence of Globigerinoides obliquus obliquus and is slightly above the last common occurrence of Discoaster kugleri, which occurs only 2.25 meters (and 3 precessional cycles) below in the studied section.